Study of interactions of mononucleotides with 1, 4-dihydropyridine vesicles using NMR and ITC techniques. (6th April 2018) - Muhamadejev, R.; Petrova, M.; Smits, R.; Plotniece, A.; Pajuste, K.; Duburs, G.; Liepinsh, E.
Abstract : The possible binding site of mononucleotides is the phosphate group with important hydrophobic interactions between the mononucleotides and the alkyl chains of DHP derivatives. Abstract : The use of 1, 4-dihydropyridine (DHP) vesicles as drug delivery agents can improve the diffusion of nucleoside and nucleotide prodrugs through the cellular membrane without degradation. Different NMR studies: spin–lattice relaxation in the rotating frame ( T 1 ρ ), saturation transfer double difference (STDD), 1 H NMR chemical shift titration, as well as isothermal titration calorimetry (ITC) experiments, showed that mononucleotides bind to 1, 4-DHP vesicles. The influence of the structure of the mononucleotides as well as that of the derivatives of 1, 4-DHP on the complexation parameters was studied.